Temperature profiles and bathymetry of some high mountain lakes - Leopold, Luna B. (National Academy of Sciences, 2000)
The ice cover in high mountain lakes breaks up and disappears in about an hour, in part because it has been divided into fragile vertical spindles, which are individual crystals. Contributing to this process are vertical holes in the ice remaining after particles of dust melt downward as they are warmed by the sun. Temperature profiles of lakes in the Wind River Mountains of Wyoming include those of five lakes in the high wilderness. All are isothermal at or near 5°C below a depth of 20 to 30 m, regardless of elevation or lake depth. Large lakes have a deeper mixed layer than do small ones because of longer fetch and thus more effective wind shear.